Seed treatment with chlorantraniliprole and carbaryl mixture for managing fall armyworm on maize: systemic synergism, control efficiency and synergistic mechanism. Issue 1 (29th October 2022) - Wang, Qinqin; Yang, Daibin; Rui, Changhui; Zhou, Lin; Li, Runan; Wang, Li; Huang, Weiling; Ji, Xuejiao; Yang, Qingjie; Liang, Pei; Yuan, Huizhu; Cui, Li
Abstract: BACKGROUND: Fall armyworm ( Spodoptera frugiperda ) is one of the major invasive pests in China, and has been widely controlled by labor‐intensive foliar sprays of agrochemicals in maize ( Zea mays L.). RESULTS: Systemic bioassay showed that mixtures of chlorantraniliprole (Chlor) and carbaryl (Carb) had dramatically synergistic effect on toxicity to S. frugiperda . Particularly, a mixture of Chlor with Carb at a mass ratio of 2:1 (MCC) exhibited the highest toxicity to S. frugiperda . Therefore, seed treatment of Chlor mixed with Carb was studied as a simple, accurate, efficient and low‐cost control technology. Our results showed that MCC treatment shortened the median lethal time and 90% lethal time to S. frugiperda compared to Chlor‐ and Carb‐alone treatments. Meanwhile, smaller leaf consumption by S. frugiperda was recorded under MCC treatment compared to Chlor‐ and Carb‐alone treatments. In field trial, maize‐seed treatment with MCC showed efficacy up to 39 days post‐emergence in preventing S. frugiperda foliar damage at a low infestation pressure. Moreover, chemical quantification by ultrahigh‐performance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS) showed that Chlor residues were more absorbed and concentrated in maize leaves of MCC treatment, compared to that of Chlor‐alone treatment. CONCLUSION: These results suggested that seed treatment with MCC can be applied to increase the control efficacy and reduce the cost of Chlor‐alone treatment for controlling S. frugiperda. The present study provided evidence of an enhanced translocation and accumulation of Chlor residues in maize leaves under MCC treatment, which likely contributed to a synergistic effect against S. frugiperda. © 2022 Society of Chemical Industry. Abstract : These results suggested that seed treatment with a mixture of Chlor with Carb at a mass ratio of 2:1 (MCC) can be applied to increase the control efficacy and reduce the cost of Chlor‐alone treatment for controlling Spodoptera frugiperda. The present study provided evidence of an enhanced translocation and accumulation of Chlor residues in maize leaves under MCC treatment, which likely contributed to a synergistic effect against S. frugiperda.